HEPATOFLUO: A prospective monocentric study assessing the benefits of indocyanine green (ICG) fluorescence for hepatic surgery. Issue 5 (23rd February 2018) - Peyrat, Patrice; Blanc, Ellen; Guillermet, Stéphanie; Chen, Yao; Ferlay, Céline; Perol, David; Basso, Valéria; Rivoire, Michel; Dupré, Aurélien
Abstract : Background and Objectives: Fluorescence imaging using indocyanine green (ICG) is undergoing extensive development. This study aimed to assess the merits of ICG in regard to hepatic surgery. Methods: Patients with liver lesions that required a resection were eligible. They received an injection of ICG the day before the surgery. Step 1 allowed assessment of use of the medical device under surgical conditions. Steps 2 and 3 assessed the capacity of the MD to detect known tumorous lesions and to spot a predefined area of the liver following injection of ICG into the portal vein (ICGp). Results: The 1st step allowed for validation of the MD use with three patients. Between 04‐2013 and 04‐2015, 45 pts were included (40 eligible) in steps 2 and 3. All of the tumorous lesions (95/119) exhibited fluorescence. Four new metastasis were detected in 3 pts, and two missing metastases in 1 pt. False positive were 22%. The maximal depth for detection by fluorescence was 13 mm. Injection of ICGp allowed the corresponding anatomical area to be identified in 16/20 patients. Conclusion: This study confirmed that intraoperative fluorescence is a helpful and relevant tool for the liver surgeon (NCT 01738217).